How representative is a time series derived from a firn core? A study at a low-accumulation site on the Antarctic plateau - Karlöf, Lars; Winebrenner, Dale P; Percival, Donald B (Journal of Geophysical Research: Earth Surface, 2006)
The acquisition and interpretation of increasingly high-resolution climate data from polar ice and firn cores motivates the question: What is the finest depth or timescale on which measurements on cores arrayed over a given area correlate? We analyze dated depth series of electrical and oxygen isotope measurements from a spatial array of firn cores with 3.5–7 km spacing in Dronning Maud Land, Antarctica, each with a temporal span of approximately 200 years. We use wavelet analysis to decompose the series into components associated with changes of averages on different scales, and thus deduce which scales are dominated by environmental noise, and which may contain a common signal. We find that common signals in electrical records have timescales of approximately 1–3 years. We identify only one electrical signal which rises significantly above the background in our 200-year records, evidently corresponding to the Tambora eruption. Several smaller signals correlate in a few of pairs of cores, one of which may correspond to a known volcanic event, but the others appear to be spurious. We present a simulation-based method for testing the significance of apparent electrical signal correlations, and highlight the importance of accurate relative dating between cores. In the case of oxygen-isotope records, we find, surprisingly, no significant correlation on any scale in the records, for any of the pairs of cores. There is, however, a weak trend toward positive correlation at longer timescales (up to 16 years). Statistical theory for the relevant confidence intervals and the observed statistics of the records permit estimation of the length of a data series necessary to reliably detect a hypothetical correlation equal to that observed. For the highest correlation observed on 16-year scales, core records of about 380 years (approximately 30 m at the Dronning Maud Land site) would be necessary to establish significance.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi; meteorologi; tidsserieanalyse

Evaluation of Global Ozone Monitoring Experiment (GOME) ozone profiles from nine different algorithms - Meijer, Yasjka; Swart, Daan P; Baier, F; Bhartia, Pawan K; Bodeker, G E; Casadio, Stefano; Chance, Kelly V; Del Frate, F; Erbertseder, T; Felder, Martin D; Flynn, Lawrence E; Godin-Beekmann, Sophie; et al. (Journal of Geophysical Research: Atmospheres, 2006)
An evaluation is made of ozone profiles retrieved from measurements of the nadir-viewing Global Ozone Monitoring Experiment (GOME) instrument. Currently, four different approaches are used to retrieve ozone profile information from GOME measurements, which differ in the use of external information and a priori constraints. In total nine different algorithms will be evaluated exploiting the optimal estimation (Royal Netherlands Meteorological Institute, Rutherford Appleton Laboratory, University of Bremen, National Oceanic and Atmospheric Administration, Smithsonian Astrophysical Observatory), Phillips-Tikhonov regularization (Space Research Organization Netherlands), neural network (Center for Solar Energy and Hydrogen Research, Tor Vergata University), and data assimilation (German Aerospace Center) approaches. Analysis tools are used to interpret data sets that provide averaging kernels. In the interpretation of these data, the focus is on the vertical resolution, the indicative altitude of the retrieved value, and the fraction of a priori information. The evaluation is completed with a comparison of the results to lidar data from the Network for Detection of Stratospheric Change stations in Andoya (Norway), Observatoire Haute Provence (France), Mauna Loa (Hawaii), Lauder (New Zealand), and Dumont d'Urville (Antarctic) for the years 1997–1999. In total, the comparison involves nearly 1000 ozone profiles and allows the analysis of GOME data measured in different global regions and hence observational circumstances. The main conclusion of this paper is that unambiguous information on the ozone profile can at best be retrieved in the altitude range 15–48 km with a vertical resolution of 10 to 15 km, precision of 5–10%, and a bias up to 5% or 20% depending on the success of recalibration of the input spectra. The sensitivity of retrievals to ozone at lower altitudes varies from scheme to scheme and includes significant influence from a priori assumptions.
Keywords: Antarktis; fjernmåling; meteorologi; ozonlaget; stratosfæren

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren